Site Selection Criteria for The Design of the Madiun Arts Facility in Madiun Regency - Selda Salma Delinda Dewi; Joko Santoso; Intan Kusumaningayu (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Madiun Regency, located in East Java, has strong cultural potential supported by various traditional arts activities. Events such as performances, exhibitions, and pencak silat championships are frequently organized by the local government, especially during cultural festivals commemorating the regency’s anniversary. However, the region still lacks adequate facilities to properly support and accommodate these activities. This study aims to determine suitable site selection criteria for developing an arts facility in Madiun Regency. The research applies a quantitative method using the Multi Criteria Decision Making (MCDM) approach. Key criteria considered include accessibility, proximity to the city center, surrounding activity intensity, compliance with spatial planning regulations, and environmental conditions. Several alternative sites were analyzed and compared based on these criteria. The results indicate that the first alternative site achieved the highest score, making it the most appropriate and strategic location for the proposed arts facility development in Madiun Regency.